2022
DOI: 10.3390/gels8030140
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic-Based Conductive Hydrogels for Electro-Active Tissues: A Review Summary

Abstract: The use of hydrogel in tissue engineering is not entirely new. In the last six decades, researchers have used hydrogel to develop artificial organs and tissue for the diagnosis of real-life problems and research purposes. Trial and error dominated the first forty years of tissue generation. Nowadays, biomaterials research is constantly progressing in the direction of new materials with expanded capabilities to better meet the current needs. Knowing the biological phenomenon at the interaction among materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Up to now, cellulose has already been extracted from readily available natural resources (such as bacteria, bamboo, jute, algae, biofilm, wood, cotton, hemp, and other plant-based materials), and is the most abundant natural macromolecular compound in the world. Five thousand to fifteen thousand glucose molecules with the molecular formula (C 6 H 10 O 5 ) n are covalently bonded together through C1 of the glucose ring and C4 of the adjacent ring ( Figure 2 a) [ 10 , 42 ], covalently bonded together by the acetal oxygen to form D-glucose with β-1,4 glycosidic bond [ 43 , 44 ]. The structure and size of natural cellulose are different in various sources, and the structural form of cellulose nanomaterials depends on processing technology.…”
Section: Cellulosementioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, cellulose has already been extracted from readily available natural resources (such as bacteria, bamboo, jute, algae, biofilm, wood, cotton, hemp, and other plant-based materials), and is the most abundant natural macromolecular compound in the world. Five thousand to fifteen thousand glucose molecules with the molecular formula (C 6 H 10 O 5 ) n are covalently bonded together through C1 of the glucose ring and C4 of the adjacent ring ( Figure 2 a) [ 10 , 42 ], covalently bonded together by the acetal oxygen to form D-glucose with β-1,4 glycosidic bond [ 43 , 44 ]. The structure and size of natural cellulose are different in various sources, and the structural form of cellulose nanomaterials depends on processing technology.…”
Section: Cellulosementioning
confidence: 99%
“…With the rapid development of the Internet of Things and the increasing demand for human-machine interfaces, flexible ionic conductors have attracted extensive attention due to their characteristics of high elasticity, transparency, adjustable mechanical properties, and consistent electrical conductivity. Cellulose-based conductive hydrogels for tissue engineering are constantly progressing [ 10 ]. Recently, conductive hydrogels showed great prospects for extensive and important applications in the field of sustainable energy such as sensors, batteries, and flexible electronic devices [ 129 ] because of their unique characteristics of sufficient flexibility, durability, and versatility.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the transition process from CI to CII is accompanied by modifications of the intensities corresponding to different crystallographic planes. The diffraction peaks characteristic of CI are presented in Figure 4a and appear at Bragg angles (2θ) of 14.6°, 16.2°, and 22.5°, which are typical for the crystallographic planes, (110), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and (200), respectively. In the case of the CII, three characteristic cellulose lattice planes were identified in the XRD diffraction pattern (Figure 4b), and these appear at 12.1° assigned to the (110) plane, at 20.1° for the (1-10) plane, and at 21.8° for (200) plane, respectively.…”
Section: Crystallinity In Cellulose Allomorphs and Cellulose-based Hy...mentioning
confidence: 99%
“…Cellulose, as one of the most abundant natural resources, has been exploited in the field of drug delivery for many years [ 1 , 2 , 3 , 4 , 5 , 6 ]. Particularly, it has a wide variety of derivatives, which have different chemical and physical properties for different drug controlled-release performances [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%